ANALISIS PENGARUH WAKTU TERBANG (PHASES OF TIME) TERHADAP BEBAN KERJA MENTAL PILOT PESAWAT TERBANG DENGAN MENGGUNAKAN METODE SUBJECTIVE WORKLOAD ASSESSMENT TECHNIQUE (SWAT) - Saputra, Abadi Dwi; Priyanto, Sigit; Munthohar, Imam; Etsem, Magda Bhinnety (FSTPT Indonesia, 2015)
The difference of flying time condition can affect a pilot's psychological condition. Regardless of the factors which the human body has a habit of working time and rest so that will affect the physical condition, and ultimately also affect the psychological condition and vice versa. The study was conducted to determine whether such a difference in mental workload on the pilot to fly a different phases of time in operating the aircraft. Mental workload measurements performed using the Subjective Workload Assessment Technique method (SWAT), this method using combine of three dimensions with their levels. The dimensions are time load, mental effort load, and psychological stress load. The results of studies shows that the condition of mental workload experienced by pilots refers to phases of time is in general (on average) in the high category (overload). While the overall showed that more pilots emphasize time factor in considering the factors of mental workload. The most burdensome conditions of a flight when the pilot was conducted in the morning (06.am - 11:59 am)), on weekends and during peak seasons.